경북지방 아까시나무 조림지의 식생유형과 생태적 특성 - 송재순; Jae-soon Song; 김학윤; Hak-yun Kim; 김준수; Jun-soo Kim; 오승환; Seung-hwan Oh; 조현제; Hyun-je Cho (한국산림과학회지, 2023)
본 연구는 경북 일대 산지 아까시나무림의 자연성 회복을 위한 생태적 관리에 필요한 기초정보 제공을 위하여 총 200개 임분에서 수집된 식생자료를 바탕으로 이원지표종분석법(TWINSPAN)으로 식생유형을 분류하고, DCA 분석으로 환경구배에 따른 그 공간배열 상태를 파악함과 아울러 식생유형별 군락적합도(Φ) 판정으로 결정된 진단종을 기준으로 군락조성요약표를 작성하였다. 식생유형은 신갈나무-둥굴레형, 밤나무-청미래덩굴형, 철쭉-인동덩굴형, 찔레꽃-쑥형, 감태나무-댕댕이덩굴형, 참느릅나무-팽나무형, 그리고 귀룽나무-푼지나무형 등 모두 7개 유형으로 분류되었으며, 대개 해발고도, 수분 체계, 천이 단계 및 교란 체제 등 복합적 요인의 차이를 반영하고 있었다. 구성종의 평균상대중요치는 아까시나무(39.7)가 단연 높게 나타났지만, 굴참나무, 졸참나무, 신갈나무, 상수리나무, 갈참나무 등 참나무류가 상위중요치 구성종으로 나타나고 있어 잠재천이경향을 가늠할 수 있었다. 또한, 식생유형별 구성종의 총피도, 생활형 조성, 종다양성 지수, 그리고 지표종 등도 비교하였다. This study was established to provide basic information necessary for ecological management to restore the naturalness of black locust (Robinia pseudoacacia L.) plantations located in the mountains of Gyeongbuk, Korea. Using vegetation data collected from 200 black locust stands, vegetation types were classified using the TWINSPAN method, the spatial arrangement status according to the environmental gradient was identified through DCA analysis, and a synoptic table of communities was prepared based on the diagnostic species determined by determining community fidelity (Φ) for each vegetation type. The vegetation types were classified into seven types, namely, Quercus mongolica-Polygonatum odoratum var. pluriflorum type, Castanea crenata-Smilax china type, Clematis apiifolia-Lonicera japonica type, Rosa multiflora-Artemisia indica type, Quercus variabilis-Lindera glauca type, Ulmus parvifolia-Celtis sinensis type, and Prunus padus-Celastrus flagellaris type. These types usually reflected differences in complex factors such as altitude, moisture regime, successional stage, and disturbance regime. The mean relative importance value of the constituent species was highest for black locust (39.7), but oaks such as Quercus variabilis, Q. serrata, Q. mongolica, Q. acutissima, and Q. aliena were also identified as important constituent species with high relative importance values, indicating their potential for successional trends. In addition, the total percent cover of constituent species by vegetation type, life form composition, species diversity index, and indicator species were compared.